Is carrot consumption associated with a decreased risk of lung cancer? A meta-analysis of observational studies. Issue 5 (14th September 2019) - Xu, Hongbin; Jiang, Heng; Yang, Wei; Song, Fujian; Yan, Shijiao; Wang, Chao; Fu, Wenning; Li, Hui; Lyu, Chuanzhu; Gan, Yong; Lu, Zuxun
Abstract: Findings of epidemiological studies regarding the association between carrot consumption and lung cancer risk remain inconsistent. The present study aimed to summarise the current epidemiological evidence concerning carrot intake and lung cancer risk with a meta-analysis. We conducted a meta-analysis of case–control and prospective cohort studies, and searched PubMed and Embase databases from their inception to April 2018 without restriction by language. We also reviewed reference lists from included articles. Prospective cohort or case–control studies reporting OR or relative risk with the corresponding 95 % CI of the risk lung cancer for the highest compared with the lowest category of carrot intake. A total of eighteen eligible studies (seventeen case–control studies and one prospective cohort study) were included, involving 202 969 individuals and 5517 patients with lung cancer. The pooled OR of eighteen studies for lung cancer was 0·58 (95 % CI 0·45, 0·74) by comparing the highest category with the lowest category of carrot consumption. Based on subgroup analyses for the types of lung cancer, we pooled that squamous cell carcinoma (OR 0·52, 95 % CI 0·19, 1·45), small-cell carcinoma (OR 0·43, 95 % CI 0·12, 1·59), adenocarcinoma (OR 0·34, 95 % CI 0·15, 0·79), large-cell carcinoma (OR 0·40, 95 % CI 0·10, 1·57), squamous and small-cell carcinoma (OR 0·85, 95 % CI 0·45, 1·62), adenocarcinoma and large-cell carcinoma (OR 0·20, 95 % CI 0·02, 1·70) and mixed types (OR 0·61, 95 % CI 0·46, 0·81). Exclusion of any single study did not materially alter the pooled OR. Integrated epidemiological evidence from observational studies supported the hypothesis that carrot consumption may decrease the risk of lung cancer, especially for adenocarcinoma.